Not a minute more : ending violence against women (UNIFEM New YorkUS, 2003)
Describes the work the UNIFEM has done and work that it has committed to for over a decade. Shows that the campaign to end violence against women has reached a new stage. Indicates the many partnerships and collaborations that are already addressing violence against women in a multi-sectoral broad-based manner.
Keywords: VIOLENCE